CHALLENGES AND PERSPECTIVES FOR SCIENTIFIC AND TECHNOLOGICAL EDUCATION IN THE 21ST CENTURY: APPROXIMATIONS BETWEEN EDGAR MORIN AND HANS JONAS - Tamiosso, Raquel Tusi; Pigatto, Aline Grohe Schirmer; Alves, Marcos Alexandre (VIDYA, 2024)
This paper analyzes the convergence between the epistemologies of Edgar Morin and Hans Jonas, and presents reflections and educational propositions related to science, technology, and life. Today’s changes can quickly make knowledge and technologies obsolete, generate uncertainty about what is to come, and require ethical decision-making and action. Education is a resource to face uncertainties, in which students need to be encouraged to understand the complexity of the world and recognize themselves as part of nature, to avoid putting life on the planet at risk. In this sense, the text presents aspects of Morin’s epistemology and Jonas’s epistemology, as well as the convergences between them that contribute to facing the challenges of contemporary education. Finally, a conception of education that breaks with the strictly anthropocentric perspective and develops a bio-cosmocentric vision is sustained.